2020
DOI: 10.3390/ijerph17072208
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gig Workers’ Psychological Contract Fulfillment on Their Task Performance in a Sharing Economy—A Perspective from the Mediation of Organizational Identification and the Moderation of Length of Service

Abstract: Workers’ isolation may occur in gig employment in the sharing economy, which generates a weak perception of the organization and unpredictable work performance. Drawing on social exchange theory, this paper proposes a framework to explore the effect of psychological contract fulfillment on gig workers’ task performance from the perspective of the mediation of organizational identification and the moderation of the length of service. A total of 223 samples were recruited from Didi (a ride-hailing company in Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 85 publications
2
61
1
Order By: Relevance
“…Prior studies have suggested that psychological contracts can lead to employees' community identification, thereby motivating their knowledge contribution behaviors (Liu et al, 2020 ). Given this, our study examines how community identification mediates the relationship between psychological contracts and knowledge contribution by using a bootstrapping method to verify the mediation effect.…”
Section: Structural Model Resultsmentioning
confidence: 99%
“…Prior studies have suggested that psychological contracts can lead to employees' community identification, thereby motivating their knowledge contribution behaviors (Liu et al, 2020 ). Given this, our study examines how community identification mediates the relationship between psychological contracts and knowledge contribution by using a bootstrapping method to verify the mediation effect.…”
Section: Structural Model Resultsmentioning
confidence: 99%
“…Organizational identification was extensively found to mediate the effects of a wide range of moral organizational and leadership dimensions on many different work outcomes (such as performance, motivational, and behavioral ones) ( Islam et al, 2019 ; Malik et al, 2019 ; Zappalà et al, 2019 ; Liu et al, 2020 ; Miao and Zhou, 2020 ). Moreover, drawing on the social identity approach and recent indications regarding moral identity, and perceptions about culture, climate, and supervisors’ values, OI can be considered as an antecedent of the interlocking processes of sense-giving and sense-making which help self-categorization as an organizational member ( Van Knippenberg and Sleebos, 2006 ; Hardy and Carlo, 2011 ; Ellemers and Haslam, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, researchers go beyond the simple reason for the cause and effect of a relationship and try to understand what bridges causality (Rose et al, 2004, Amery andZumbo, 2008). A number of authors (Liu et al, 2020, Ma et al, 2020 pay close attention to the moderating variables in research. Moderator is a qualitative or quantitative variable that affects the direction or intensity of the relation of a predictive variable (independent) and another dependent one (MacKinnon, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…The first one is the discrepancy between the fields of study, the number of students admitted to them and the needs of the labour market. According to the Kuchař (2007), the differences in the employability of graduates of various fields on the labour market will deepen further. Since the early 1990s, economic fields of study have been significantly preferred.…”
Section: Introductionmentioning
confidence: 99%